2000
DOI: 10.1016/s1074-5521(00)00075-2
|View full text |Cite
|
Sign up to set email alerts
|

The biosynthetic gene cluster for the microtubule-stabilizing agents epothilones A and B from Sorangium cellulosum So ce90

Abstract: The overall architecture of the gene cluster responsible for epothilone biosynthesis has been determined. The availability of the cluster should facilitate the generation of designer epothilones by combinatorial biosynthesis approaches, and the heterologous expression of epothilones in surrogate microbial hosts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
235
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 295 publications
(237 citation statements)
references
References 75 publications
1
235
0
1
Order By: Relevance
“…Ixabepilone (Ixempra; Bristol-Myers Squibb), an analogue of epothilone B, has been recently approved in the treatment of breast cancer 165 . The biosynthetic gene clusters of epothilones have been widely studied 166,167 . Recently, a 56 kb epothilone biosynthetic gene cluster was reassembled using unique restriction sites (which allowed for future module interchangeability) in the guanine-and cytosine-rich host Myxococcus xanthus 168 .…”
Section: Applyingmentioning
confidence: 99%
“…Ixabepilone (Ixempra; Bristol-Myers Squibb), an analogue of epothilone B, has been recently approved in the treatment of breast cancer 165 . The biosynthetic gene clusters of epothilones have been widely studied 166,167 . Recently, a 56 kb epothilone biosynthetic gene cluster was reassembled using unique restriction sites (which allowed for future module interchangeability) in the guanine-and cytosine-rich host Myxococcus xanthus 168 .…”
Section: Applyingmentioning
confidence: 99%
“…An analysis of conserved catalytic motifs in the related methyltransferases shows that none of the metazoan FASs contains an intact set of catalytic residues, in agreement with the observation that these enzymes do not methylate their products and are not SAM-dependent. However, in related fungal and bacterial polyketide synthases, intact homologues of this domain are found in equivalent positions and are leading to the production of (partially) methylated products (Edwards et al 2004 ;Fujii et al 2005 ;Molnar et al 2000). The significance of the yME domain for animal FAS remains unclear ; it is probably a remnant from an evolutionary precursor multienzyme producing branched fatty acids or polyketides, and it may still play a steric or stabilizing role for the overall functioning of the enzyme.…”
Section: Domain Structuresmentioning
confidence: 99%
“…The phlE gene, located at the 39 end of the phlACBD operon in P. fluorescens strains (Bangera & Thomashow, 1996Delany, 1999) encodes a putative transmembrane permease with 12 predicted transmembrane segments (TMS) (Bangera & Thomashow, 1999 transporter mediating resistance to a range of structurally dissimilar drugs (Paulsen & Sukurray, 1993;Yoshida et al, 1990). PhlE also has structural similarity with integral membrane proteins associated with resistance which are encoded within clusters responsible for polyketide biosynthesis (Brautaset et al, 2000; Fernandez-Moreno et al, 1991;Guillfoile & Hutchinson, 1992;Marger & Saier, 1993;Molnar et al, 2000). It has been reported that phlE mutants produce less PHL than the parent strain (Bangera & Thomashow, 1996.…”
Section: Introductionmentioning
confidence: 99%